To Serve the President : Continuity and Innovation in the White House Staff - Patterson, Bradley H. (Bradley Hawkes), 1921-2020 (Book collections on Project MUSE., 2008)
"Opens a window onto the closely guarded Oval Office turf: the operations, offices, and people of the complete White House team. Describes its organizational structure, recent innovations made in the face of changing events, what people do, while revealing the total size and cost of the contemporary White House team"--Provided by publisher